John Piper et Benjamin Britten : le renouveau de l’opéra anglais et ses décors - Sophie Aymès (Revue LISA)
From 1946 the artist John Piper designed sets for eight of Benjamin Britten’s operas. In this article, John Piper’s contribution to the renaissance of English opera is considered in the wider context of the artistic and political reconstruction of England after the Second World War. During the War, Piper was one of the artists who redefined Englishness. As an abstract artist turned architectural painter, he created a pastoral vision of the national heritage whose preservation had become necessary. The designs form a part of Piper’s pictorial work whose logical conclusion found expression in stained-glass windows. From the architectural designs for The Rape of Lucretia to the window he designed for the new Coventry Cathedral and to the last opera sets for Death in Venice, he created backdrops for Britten’s works that provided a sense of aesthetic continuity whilst reflecting the contradictions of opera as a social form of art in post-war Britain.